Is severe hypercalcemia immediately life-threatening?. (April 2018) - Guimard, Camille; Batard, Eric; Lavainne, Frédéric; Trewick, David
Abstract : Objective: Severe hypercalcemia is often considered an emergency because of a potential risk of cardiac arrest or coma. However, there is little evidence to support this. The aim of our study was to assess whether severe hypercalcemia (Ca>4 mmol/l or 16 mg/dl) was associated with immediately life-threatening cardiac arrhythmias or neurological complications in patients admitted to the Emergency Department (ED). Methods: A retrospective observational study was carried out over a 5-year period (2008–2012). Eligible patients were admitted to the Adult Emergency Department of Nantes University Hospital and had a calcium concentration in excess of 4 mmol/l. There were no exclusion criteria. The primary outcome was the number of life-threatening cardiac arrhythmias and/or neurological complications during the stay in the ED. The secondary outcomes were correlation between calcium concentrations/ECG QTc intervals and mortality. Results: A total of 126 204 adult patients had calcium concentrations measured. Thirty one (0.025%) patients had severe hypercalcemia as defined in our study. The median calcium concentration was 4.3 mmol/l (Q1, 4.2; Q3, 4.7) and the median albumin-adjusted calcium concentration was 4.3 mmol/l (Q1, 4.1; Q3, 4.7). No patient presented with a life-threatening cardiac event during stay in the ED. The median ED stay was 7 h 32 min. One patient presented with a coma of multifactorial origin. There was no correlation between calcemia and QTc intervals ( P =0.60). Mortality at 1 year was 55% (17 patients). Conclusion: We found no cases of immediately life-threatening cardiac arrhythmias or neurological complications associated with hypercalcemia above 4 mmol/l over a 5-year period in a large tertiary ED.